Researching terrorism, peace and conflict studies : interaction, synthesis and opposition - Tellidis, Ioannis; Toros, Harmonie, 1974- (London ; New York : Routledge, 2015)
"This book offers a succinct examination of directions of research in the fields of Terrorism Studies and Peace and Conflict Studies. With a particular focus on the interactions, differences and potential synergies between the two, it consists of theoretically- and empirically-informed contributions, which will shed light on whether the two fields can inform each other on issues of mutual interest and importance, thus strengthening both research and praxis. As such it does not shy away from the major ontological and epistemological puzzles common between the two fields, and can be used as both a reference work and a stimulus for additional research. The book does not intend to offer a comprehensive review of Terrorism and Peace and Conflict Studies, but instead focuses on what its authors consider as the most pressing areas and issues, thus opening a new debate and mapping a new agenda for synthesised, cross-pollinated research. Among the key themes this book examines are questions relating to: the conceptualisation(s) of peace and violence; the exceptionalisation of terrorist violence and its effect on the resolution or perpetuation of the conflict; the ontological and epistemological status of security; the understandings of asymmetry; the possibilities, timing and potential of negotiations between asymmetrical actors; the relationship between international, national and local actors in their contextual environments; the relationship between scholarship and political power; the dysfunctionality of the liberal peace and the opportunities offered by post-liberal peacebuilding frameworks; and the implications and challenges of cyber-terrorism and cyber-conflict. The book will also launch the debate on whether the recent critical turn in terrorism studies can offer a pathway for peace studies to engage with the so far largely ignored question of power. The Case Studies section gathers contributions not only from key scholars but also practitioners and policy makers, examining the synergies and contradictions between terrorism and peace and conflict approaches in Colombia, Sri Lanka, the Basque Country, Afghanistan, Somalia and Turkey among others. They critically assess and evaluate: the statist approach inherent in both terrorism approaches and liberal peacebuilding frameworks; their problem-solving tendencies; the role of the grassroots levels of society in the marginalisation of violence; the inefficiency of simplistic frameworks of understanding and implementation when it comes to producing self-sustainable peace(s); and the chains of governance whereby international (and transnational) actors direct national actors who in turn direct local actors. This book will be of much interest to students of terrorism studies, peace and conflict studies, research methods, security studies and IR"--
"This book examines potential synergies between the fields of Terrorism Studies and Peace and Conflict Studies. The volume presents theoretically- and empirically-informed contributions, which shed light on whether the two fields can inform each other on issues of mutual interest and importance. The book examines key themes including the conceptualisation(s) of peace and violence; the exceptionalisation of terrorist violence; the relationship between scholarship and political power; the dysfunctionality of the liberal peace and the opportunities offered by post-liberal peacebuilding frameworks; and the implications and challenges of cyber-terrorism and cyber-conflict. Furthermore, the book intends to be a launching pad for future debate on whether the recent 'critical' turn in terrorism studies can offer a pathway for peace studies to engage with the so far largely ignored question of power. Consisting of not only key scholars but also practitioners and policy makers, the contributors present a number of case studies, including Colombia, Northern Ireland, the Basque Country, and Iraq, where they explore the relationships between terrorism and peace and conflict approaches. They critically analyse the statist approach inherent in both terrorism approaches and liberal peacebuilding frameworks; the role of the grassroots levels of society; the inefficiency of simplistic frameworks of understanding and implementation; and the chains of governance from international (and transnational) actors to national actors and finally from national to local actors. This book will be of much interest to students of terrorism studies, peace and conflict studies, IR and security studies"--
Includes bibliographical references and index.
Keywords: Terrorism -- Study and teaching